Eclipse in a Philosopher's Perspective; Construction of Myth, Tawhid, and Shari'a - Anzaikhan, M. (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2023)
Eclipse is a natural phenomenon that has a variety of determinations from time to time. Historically, eclipses were first believed to be mythical events and were closely associated with the existence of gods. When Islam came, the eclipse changed into the dimensions of tawhid and Sharia. Tawhid talks about how natural phenomena show the power and existence of Allah Almighty, while the dimension of sharia is reflected in the existence of eclipse prayers in Islam. Long before Islam came, philosophers had discussed the phenomenon of eclipses, nowadays eclipses are a serious study, especially in the study of Falak. This article is classified as literature research with a qualitative approach. The methodology used is a descriptive analysis study. The results of the study concluded that eclipses in philosophers' thoughts are still connected with the dimensions of myth and sharia. The eclipse prayer service is a manifestation of tawhid as a form of gratitude and hope.